Dynamics Of Working Capital, Profitability, and Capital Structure: Implications For Corporate Sustainability in The Context Of Effective Tax Rates - Elia Rossa; Nera Marinda Machdar; Adler Haymans Manurung (International Journal of Economics, Management and Accounting, 2025)
This study aims to analyze the dynamics of working capital, profitability, and capital structure, and their implications for corporate sustainability in the context of effective tax rates. Corporate sustainability has become increasingly important in an era of global competition and stringent regulations. A review of the literature indicates that well-managed working capital can enhance profitability and provide financial flexibility, while an optimal capital structure contributes to the financial stability of the firm. Furthermore, effective tax rates play a crucial role in determining a company's profitability and investment decisions. This research identifies a gap in the existing literature, as few studies integrate these three factors within the framework of sustainability. By employing a comprehensive analytical approach, this study seeks to provide deeper insights into how the dynamics of working capital, profitability, and capital structure interact to support corporate sustainability. The findings are expected to make a significant contribution to financial management practices and sustainable corporate policies.